Cultes et sanctuaires de Crannon - Decourt, Jean-Claude (Tekmeria, 2024)
This article presents a synthesis of what literary, epigraphic, archaeological, and numismatic sources reveal about the cults and sanctuaries of ancient Krannon. What myths and legends are associated with the city’s foundation and history? Which deities were definitively or possibly worshipped there? Do any archaeological remains of sanctuaries exist within the city or its territory? And finally, can we identify Krannon’s patron deity? While many of these deities are found throughout Greece, Krannon’s pantheon shows distinctly Thessalian characteristics.